Risk of gastroenteritis among triathletes in relation to faecal pollution of fresh water - van Asperen, I. A.; Medema, G.; Borgdorff, M. W.; Sprenger, M. J.; Havelaar, A. H. (International Journal of Epidemiology, 1998)
BACKGROUND: We conducted a prospective cohort study among endurance athletes to investigate the effects of microbiological water quality on the risk of gastroenteritis after bathing in fresh waters that meet current water quality standards. We aimed to establish quantitative relationships, in order to evaluate current bathing water standards. METHODS: The study was spread over two summers, during which 827 triathletes (swimmers) in seven Olympic distance triathlons and 773 participants in 15 run-bike-runs (non-swimming controls) participated. Intensive water quality monitoring was used to assess exposure to faecal indicator organisms and detailed questionnaires were used to collect data on the occurrence of health complaints and potential confounding factors. RESULTS: The microbiological water quality at the time of the triathlons met current Dutch and European bathing water standards. Dependent on the case definition studied, gastroenteritis developed in 0.4-5.2% of swimmers and 0.1-2.1% of non-swimmers in the week following exposure (odds ratio [OR] = 1.6-2.3). Attack rates and burden of disease varied with the case definition used. Among swimmers, the attack rate of gastroenteritis was significantly increased when the geometric mean concentration of thermotolerant coliforms in the water at the time of exposure was > or = 220/100 ml or the geometric mean concentration of Escherichia coli was > or = 355/100 ml (OR comparing high versus low exposure 2.9-4.7 dependent on the case definition studied). Thermotolerant coliform concentrations at these triathlons ranged from 100/100 ml (the EU guide level) to 960/100 ml (the EU imperative level is 2000/100 ml). Below the threshold levels attack rates were comparable with attack rates among non-swimmers. A relation with other indicators of faecal pollution was not observed. CONCLUSIONS: We observed that swimming in fresh waters that met the European imperative level for thermotolerant coliforms but failed the European guide level was associated with a significant risk of gastroenteritis among triathletes. This means that the current European imperative level for thermotolerant coliforms provides insufficient protection to gastrointestinal illness for those who are comparable with triathletes.